2007
DOI: 10.1111/j.1083-6101.2007.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Peer Feedback to Enhance the Quality of Student Online Postings: An Exploratory Study

Abstract: This study investigates the impact of peer feedback used as an instructional strategy to increase the quality of students' online postings. While peer feedback has been demonstrated to support students' learning in traditional classrooms, little is known about its efficacy in online discussions. To address this gap, we examined students' perceptions of the value of giving and receiving peer feedback, specifically related to the quality of discussion postings in an online course. In addition, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(172 citation statements)
references
References 13 publications
9
150
0
13
Order By: Relevance
“…The results of the content analysis showed that when students employed the role-play strategy to provide peer feedback, their comments were likely to identify problems, ask questions, and provide suggestions, in addition to showing support. Previous studies indicate that learners are least likely to identify problems in their peers' work when they are not being prompted to do so, or when they do not adopt a role-play strategy (Ching, 2014;Ching & Hsu, 2013b), due to cognitive and interpersonal reasons (e.g., Ertmer et al, 2007). Affirming previous findings in Ching (2014), the results of this study demonstrated that the use of the role-play strategy resulted in a high percentage of feedback entries containing problem identification.…”
Section: The Impact Of Role-playing On the Types Of Peer Feedback Promentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the content analysis showed that when students employed the role-play strategy to provide peer feedback, their comments were likely to identify problems, ask questions, and provide suggestions, in addition to showing support. Previous studies indicate that learners are least likely to identify problems in their peers' work when they are not being prompted to do so, or when they do not adopt a role-play strategy (Ching, 2014;Ching & Hsu, 2013b), due to cognitive and interpersonal reasons (e.g., Ertmer et al, 2007). Affirming previous findings in Ching (2014), the results of this study demonstrated that the use of the role-play strategy resulted in a high percentage of feedback entries containing problem identification.…”
Section: The Impact Of Role-playing On the Types Of Peer Feedback Promentioning
confidence: 99%
“…The issue of lacking psychological safety is commonly evidenced in peer review activities where students felt uncomfortable or anxious about critiquing other's work because they believed that critique may ruin the relationship (Ellison & Wu, 2008;Ertmer et al, 2007;Topping, Smith, Swanson, & Elliot, 2000). Anonymity has been used to improve psychological safety in the peer feedback activities, aiming to create an environment that students feel more comfortable to offer critical and constructive feedback.…”
mentioning
confidence: 99%
“…Therefore, it is possible that the students were not prepared for higher quality discussions and there was a lack in effective guidance and stimulations of high-order thinking. The latter could potentially be supported via activities such as problems' creations and solutions (Tofade, Elsner, & Haines, 2013), situation-related topic discussions (Wang, Wen, & Rosé, 2016), feedback exchange among teachers and students (Ertmer et al, 2007), or assessment of discussion contributions (Klisc, McGill, & Hobbs, 2017), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Through this interactive process, learners collaboratively construct knowledge when they clarify their own thinking and gain multiple perspectives on a given issue, which enables the creation of more comprehensive and deeper understanding toward learning. (Ertmer, et al, 2007). When providing feedback, learners actively engage in articulating their evolving understanding of the subject matter (Liu & Carless, 2006).…”
Section: Rationale For Adopting Peer Feedbackmentioning
confidence: 99%
“…Feedback has been suggested as one of the crucial instructional components for improving knowledge and skill acquisition, and for motivating learning (Shute, 2008). The lack of feedback can impact students' learning adversely and it has been argued as a reason for students' withdrawing from online courses (Ertmer, et al, 2007). Some research findings suggested that feedback may be more important in online learning environments than in face-to-face learning environments (Lynch, 2002;Palloff & Pratt, 2001), due to the lack of regular face-to-face interaction in the former.…”
Section: Introductionmentioning
confidence: 99%